Literature Review: Analysis of Democratic Leadership Styles - Fibriyanti Daud; Andi Indriani Ibrahim; Syahbudin Adam; Salma A; Putri Aulia Duhi; Karmila Sibula; Nidyawati (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
uman resources (HR), including teachers, staff, and employees, play a crucial role in determining the success of an organisation's vision, mission, and objectives. Optimal HR performance is greatly influenced by a positive work environment and leadership attitudes. Democratic leadership style, characterised by encouraging active participation of members, involvement in decision-making, and a focus on deliberation, is widely believed to be one of the most effective approaches to creating a conducive work environment. This literature review aims to synthesise the main findings from various studies exploring the influence of democratic leadership styles. The main focus is to analyse the impact of democratic leadership on performance (teachers, staff, and employees), organisational commitment, work motivation, and psychological empowerment in various contexts, including education, government, and business. The method used in this review is a synthesis of 20 scientific journal articles. The majority of these studies used a quantitative approach, in which data was collected through questionnaires and analysed using multiple regression techniques (T and F tests) to test the influence of variables. Most of the other studies used literature studies or systematic literature reviews (SLRs) to analyse, categorise, and verify findings from various existing research sources. There were also studies with a descriptive qualitative approach that used in-depth interviews and observations to describe the implementation of democratic leadership in the field. The findings from the majority of studies consistently show that democratic leadership styles have a positive and significant effect on dependent variables. These positive effects include: Performance: Democratic leadership has a positive and significant effect on the performance of teachers and employees in both the government and business sectors. In a multicultural work environment, democratic leadership has been proven to be effective in improving team performance. Psychological Variables & Work Attitude: Democratic leadership is also found to have a significant effect on increasing organisational commitment and contributing to the psychological empowerment of employees. This is in line with its ability to create a conducive work environment and strengthen leader-subordinate relationships. Mediation/Moderation Variables: The influence of democratic leadership on performance is often reinforced or mediated by other variables such as work motivation and work ethic. Combining it with other styles, such as visionary leadership, is also recommended for maximum effectiveness, especially in the digital age. This literature review concludes that democratic leadership style is a strong determinant in improving organisational effectiveness and performance. Leaders who apply this approach, emphasising deliberation, active participation, and open communication, will succeed in fostering motivation, commitment, and psychological empowerment, which will ultimately have a significant impact on improving the performance of teachers, staff, and employees. The main recommendation is for organisations, including educational and government institutions, to implement and strengthen democratic leadership styles to achieve their strategic goals.